Analisis Kelayakan Investasi Pendirian Corn Drying Centre oleh Perum BULOG: Kajian Empiris di Kabupaten Dompu - Embun Suryani; Syahrul Syahrul; Sukmawati Sukmawati (Universitas Mataram, 2022)
This empirical study was conducted to obtain a detailed description of the investment feasibility as well as to determine the level of profit that can be obtained from the Corn Drying Center in Dompu Regency. The research was conducted in Dompu Regency, NTB. The data collection method in this research is a case study by analyzing the investment feasibility of establishing a CDC by Perum BULOG in Dompu Regency. While the data collection techniques are documentation, observation and in-depth interviews with key informants. The results showed that at the production capacity of 34,500 tons per year, the calculation of the NPV showed positive. While the calculation of Net B/C is greater than 1 with an IRR rate greater than the Bank's deposit interest, namely 22.05% with a payback period of 4.98 years. For this reason, in general, the investment in Dompu CDC development based on financial aspects (NPV, Net/BC, IRR, PP) is considered very feasible. Financial analysis also shows that a decrease in production capacity also needs to be anticipated, where the limit for a decrease in production capacity that can be tolerated is up to 24,100 tons per year